Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
P = x^3 (z-y^2) +y^3(x-z^2)+z^3(y-x^2)+xyz(xyz-1)
= -x^3 (y^2-z) +y^3x-y^3z^2 +z^3y-z^3x^2+x^2y^2z^2-xyz
= -x^3 (y^2-z)+(y^3x-xyz)-(y^3z^2-z^3y)+(x^2y^2...
= -x^3 (y^2-z)+xy(y^2-z)-yz^2(y^2-z)+x^2z^2(y^2...
= (y^2-z)(-x^3+xy-yz^2+x^2z^2)
= (y^2-z)[-x(x^2-y)+z^2(x^2-y)]
= (y^2-z)(x^2-y)(z^2-x) = b. a. c ko phụ thuộc vào biến
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có: \(a^3+b^3=\left(a+b\right)^3-3ab\left(a+b\right)\)
\(\Rightarrow x^3+y^3+z^3=\left(x+y\right)^3+z^3-3xy\left(x+y\right)\)
\(=\left(x+y+z\right)^3-3\left(x+y\right)z\left(x+y+z\right)-3xy\left(x+y\right)\)
\(=0-3xy\left(x+y\right)\)( do x+y+z=0)
Lại có \(x+y+z=0\Leftrightarrow x+y=-z\)
\(\Rightarrow x^3+y^3+z^3=3xyz\)
Vậy \(B=\frac{3xyz}{-xyz}=-3\)
\(B=\dfrac{x}{y}\cdot\dfrac{1}{2z}\cdot xyz\cdot\left(\dfrac{x^3}{yz^2}+y\right)\)
\(=\dfrac{x^2yz}{2yz}\cdot\dfrac{x^3+y^2z^2}{yz^2}\)
\(=\dfrac{x^2}{2}\cdot\dfrac{1}{yz^2}\cdot\left(x^3+y^2z^2\right)=\dfrac{x^2}{2yz^2}\cdot\left(x^3+y^2z^2\right)\)